2021
DOI: 10.1371/journal.pone.0251179
|View full text |Cite
|
Sign up to set email alerts
|

Social media and public perception as core aspect of public health: The cautionary case of @realdonaldtrump and COVID-19

Abstract: The social media milieu in which we are enmeshed has substantive impacts on our beliefs and perceptions. Recent work has established that this can play a role in influencing understanding of, and reactions to, public health information. Twitter, in particular, appears to play a substantive role in the public health information ecosystem. From July 25th, 2020 to November 15th, 2020, we collected weekly tweets related to COVID19 keywords and assessed their networks, patterns and properties. Our analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…Social media platforms such as Instagram have altered the way, in which people receive and engage with health information (Chen & Wang, 2021; Goodyear et al, 2019). Moreover, health information shared social media can impact public beliefs, perceptions and attitudes toward health issues (Fuentes & Peterson, 2021; Ugarte et al, 2021; Zou et al, 2021), with patient influencers additionally providing valuable insights on specific health issues (Heiss & Rudolph, 2022). Thus, we were specifically interested in the way, in which patient influencers frame health responsibilities—verbally and visually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media platforms such as Instagram have altered the way, in which people receive and engage with health information (Chen & Wang, 2021; Goodyear et al, 2019). Moreover, health information shared social media can impact public beliefs, perceptions and attitudes toward health issues (Fuentes & Peterson, 2021; Ugarte et al, 2021; Zou et al, 2021), with patient influencers additionally providing valuable insights on specific health issues (Heiss & Rudolph, 2022). Thus, we were specifically interested in the way, in which patient influencers frame health responsibilities—verbally and visually.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are potential benefits, too, as social media enable users to share their personal health-related experiences, thoughts, and feelings with others and receive social support from them (Chen & Wang, 2021; Smailhodzic et al, 2016; Zhao & Zhang, 2017). Moreover, health information on social media can impact public beliefs, perceptions and attitudes toward health issues (Fuentes & Peterson, 2021; Ugarte et al, 2021) as well as mobilize social resources (Chen & Wang, 2021).…”
Section: Patient Influencers On Social Mediamentioning
confidence: 99%
“…Researchers have previously examined the role public figures on social media have in shaping the public’s health beliefs. Prior studies have found that only a handful of individual accounts can be responsible for disseminating information and misinformation that is then shared or retweeted thousands of times, reaching potentially millions of social media users [ 11 ]. Furthermore, a 2013 meta-analysis found that individuals are conditioned to react positively to the advice of celebrities, and that celebrity medical advice can be a contagion that diffuses throughout social networks [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social media represented an ideal platform to spread information quickly and has been used to rapidly disseminate information during previous public health emergencies and disease outbreaks, including Ebola, H1N1 (swine flu) and MERS-CoV outbreaks [10][11][12][13]. In addition, social media analytics have been used to better understand public perceptions and responses to emerging infectious diseases [14].…”
Section: Introductionmentioning
confidence: 99%